Konversi Kapal Sabuk Nusantara 48 Menjadi Kapal Rumah Sakit di Wilayah Kepulauan Riau - Andrizal; Baihaque, Muhd Ridho; Uzri H.A.NST, Islam; Zuriana, Fitri; Panggalaira, Kurnia; Febrianto, Putra Aidil; Adeyandra, Alveiro (Sustainable, 2023)
Health Facilities in the Riau Islands Province still not reachable at Riau Islands territorial. Many people still don’t have access to get health. This study aims to convert MV Sabuk Nusantara 48 which operating in Riau Archipelago Area into a Type C Hospital Ship become one of health facilities and able to reach remote islands in The Riau Archipelago. Ship design modification only made on the inside of vessel according to the requirement of Type C hospital without change the Ship structure therefore hydrostatic analysis, machinery, and Ship resistance not have significant deference. The result of the conversion of this ship possible to became a health facility that can accommodate health problems in remote area of the Riau Islands